2014
DOI: 10.1159/000358484
|View full text |Cite
|
Sign up to set email alerts
|

Decreases in Energy and Increases in Phase Locking of Event-Related Oscillations to Auditory Stimuli Occur during Adolescence in Human and Rodent Brain

Abstract: Synchrony of phase (phase locking) of event-related oscillations (EROs) within and between different brain areas has been suggested to reflect communication exchange between neural networks and as such may be a sensitive and translational measure of changes in brain remodeling that occur during adolescence. This study sought to investigate developmental changes in EROs using a similar auditory event-related potential (ERP) paradigm in both rats and humans. Energy and phase variability of EROs collected from 38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 120 publications
(114 reference statements)
5
16
0
Order By: Relevance
“…In particular, even after accounting for the effects of volume conduction on brain electric signals, the density and spatial variability of alpha-band cortical networks increased in late childhood – this trend likely continues to mature into young adulthood (Uhlhaas et al, 2010). Taken together, these findings are consistent with evidence demonstrating that the maturing brain is characterized by an enhanced ability to maintain phase synchronized brain oscillations within specific frequency ranges (Ehlers et al, 2014; Poulsen, Picton, & Paus, 2009; Uhlhaas et al, 2009). The ability to sustain precise patterns of neuronal coordination ( i.e.…”
Section: Discussionsupporting
confidence: 89%
“…In particular, even after accounting for the effects of volume conduction on brain electric signals, the density and spatial variability of alpha-band cortical networks increased in late childhood – this trend likely continues to mature into young adulthood (Uhlhaas et al, 2010). Taken together, these findings are consistent with evidence demonstrating that the maturing brain is characterized by an enhanced ability to maintain phase synchronized brain oscillations within specific frequency ranges (Ehlers et al, 2014; Poulsen, Picton, & Paus, 2009; Uhlhaas et al, 2009). The ability to sustain precise patterns of neuronal coordination ( i.e.…”
Section: Discussionsupporting
confidence: 89%
“…The S -transform magnitude squared for a time/frequency interval is therefore proportional to volts squared. These analyses are similar to what has been previously described (Ehlers et al, 2014). …”
Section: 0 Methodssupporting
confidence: 87%
“…For example, Gaetz et al(64) observed greater movement-related motor cortex gamma synchrony in adolescent (11- to 13-years-old) versus younger children (4- to 6-years-old), suggesting a more general phenomena. Maturation of neural oscillatory activity is, of course, observed in frequencies below gamma (e.g., (65-67)), with a recent translational study (human and rat) suggesting that increased neural synchrony may be a general feature of neural network maturation(68). …”
Section: Discussionmentioning
confidence: 99%